Roadmap to inclusive Artificial Intelligence for persons with intellectual disability (Journal of Accessibility and Design for All, 2025)
The rapid evolution of Artificial Intelligence (AI) poses significant opportunities and challenges for historically discriminated groups, such as persons with intellectual disabilities. This article proposes a conceptual framework that enables an inclusive and accessible approach to designing generative AI systems. Based on an exhaustive review of legislative, socio-health, and technological sources, key concepts such as disability, accessibility, and usability are defined and related, with intellectual disability serving as the central objective of this work. The need to apply principles of Universal Design (UD) and User-Centred Design (UCD) is highlighted to ensure products, environments, and services that are understandable, usable, and customisable. Finally, specific challenges are identified in the development of generative AI tools in Spain for persons with intellectual disabilities, and specific recommendations are proposed to promote inclusive AI for all.